POTRET KONDISI PERAIRAN DI PULAU KARANG CONGKAK KEPULAUAN SERIBU, DKI JAKARTA - Riyadi, Agung (Center for Environmental Technology, 2018)
Pulau Panggang in Kepulauan Seribu district have many small corall island sand, many reef flat the island. Approximately have four island reefs and there are relatively wide, that are a P. Karang Semak Daun, P. Karang Beras, P. Karang Congkak and P. Karang Bongkok. Karang Congkak Island has reef flat and its area is more than 169,36 Ha, while land area is just only 0,6 Ha and 0,5 – 2 meter depth. Water quality include temperature distribution about 29,8 – 30,4 oC, dissolved oxygen 6,001 – 7,110 mg/L, salinity 32,891 – 33,214 PSU, turbidity 0,518 – 1,944 FTU,chlorophyll 0,204 – 0,563 ug/L and pH about 8,505 -8,592 and its quality relative normal. Current velocity about 0,102 – 0,407 m/s at the reef flat, this conditions is relative height all along monsoon until corall reff many a massive type, at the some location have good corall conditon. Karang Congkak Island has potency for tourism maritime. Determining of sea protection at Karang Congkak island is very useful to preserve remainder corall reef existence. Keywords : reef flat, waters quality, preserve area